LATE BARREMIAN-EARLY APTIAN AMMONITES FROM THE MAIOLICA FORMATION NEAR CESANA BRIANZA (LOMBARDY BASIN, NORTHERN ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 1994)
The ammonite faunas collected in three marly interbeds of the Maiolica limestone exposed near Cesana Brianza (Como province, Lombardy) are described in this paper. The age of the first and second interbeds is Late Barremian. In particular the first is tentatively ascribed to the sartousi zone and the second to the feraudi/giraudi zones. The new specíes Toxoceratoides sudalpinus sp. n. has been collected in the second level. The fauna of the youngest interbed does not allow us to recognize a specific ammonite zone, although it can be ascribed to the Barremian-Aptian boundary or even the basal Aptian. It is characterized by the occurrence of Leptoceratoidinae which were not reported before from this stratigraphic level.